PSXII-27 Determining the potential usefulness of different metrics of eating behavior in relation to growth performance of fattening Holstein bulls. - Devant, M (J Anim Sci, 2018)
The continuous progress on technology development allows capturing a number of traits regarding eating behavior. However, the ability of measuring a given trait does not imply that the particular trait is relevant to animal production. Thus, there is a need to assess what available eating behavior data are potentially linked to animal performance. The main objective of fattening Holstein bulls is to maximize feed intake without impairing feed efficiency (i.e., reducing days on feed to obtain the target BW) or improving feed efficiency maintaining growth. The fattening starts with a growing phase (from 150 kg to 350 kg of BW) and ends with a finishing phase with a final BW between 450 to 650 kg). The present study evaluated the relationship between eating pattern and performance in Holstein bulls fed high-concentrate diets. A database of 9,500 eating behavior records corresponding to 1,320 bulls from 11 studies was built. The relationships between different metrics of eating behavior (i.e., meal size, meal frequency, meal duration, etc...) and performance were evaluated by regression analyses using the fit model procedure of JMP(®).During the growing phase, eating rate was quadratically and negatively correlated with feed efficiency, with a lowest feed efficiency obtained when eating rate was 110 g/min. Eating rate explained 26% of the observed variation in efficiency (P < 0.01). During the finishing phase, meal size was quadratically and negatively correlated with the number of meals and explained 70% of variation in the number of meals (P < 0.01), with the lowest number of meals obtained with a meal size of about 1–1.4 kg of DM. During the growing phase, decreasing eating rate can be a strategy to improve feed efficiency, and during the finishing phase, large meal sizes should be avoided to maximize number of meals and thus feed intake.